Effect of Tillage and Weed Control Methods in Maize (Zea mays) -Wheat (Triticum aestivum) Cropping System - Upasani, R. R.; Barla, Sheela; Puran, A. N. (International Journal of Bio-resource and Stress Management, 2017)
An experiment was conducted to find out the effect of tillage and weed control methods on weed dynamics and productivity of maize (Zea mays L.) -wheat (Triticum aestivum L.) cropping system. The treatments comprised of combinations of tillage sequences in main plots and weed control methods in sub plots. The results revealed that zero tillage in rainy and winter season is as good as conventional tillage method in reducing weed dry matter and producing maize and system yield, while, conventional tillage in rainy and winter seasons (CT-CT) and conventional tillage in rainy and zero tillage in winter (CT-ZT) reduced weed density as well as weed dry weight in wheat crop consequently, higher wheat grain yield was recorded compared to rest of the tillage sequences. Integrated weed management performed in maize and wheat (IWM-IWM) sequence recorded 51.78% and 61.96% higher maize grain yield and net return of maize, 18.40% and 17.23% higher wheat grain yield and net return of wheat, 31.78% and 34.96% higher system yield and net return respectively, compared to weedy check. Zero tillage with or without residue recorded improved soil pH, organic carbon, CO2 and dehydrogenase activity. IWM in both the crops recorded higher yields, while significantly higher B:C ratio was under recommended herbicide i.e. atrazine 1.0 kg ha-1 pre emergence in maize and 2,4-D 0.5 kg ha-1 post emergence in wheat (RH-RH). IWM-IWM improved soil CO2 and dehydrogenase activity than RH-RH sequences from their initial values.